Community Initiatives for Prisoners (Archives of Criminology, 1992)
Assistance to persons released from prison is considered an indispensable stage of the process of carrying out the penalty of imprisonment. The authors engaged in that subject agree as to the role of postpenitentiary assistance  in reduction of relapse into crime and its connection with social readjustment of offenders. In my opinion, that approach is insufficient for a full justification of the actual sense of assistance rendered to persons on release from prison.Pragmatic researchers treat the slogan of helping prisoners as obvious and focus on the related legal and organizational problems. Lacking strict criteria of appraisal, the analysis of legal solutions resolves itself usually into approving comments and to attributing the indolent functioning of the assisting agencies to sluggishness of the actual care providers. The suggested conceptions of improvement of the  after-care resolve themselves into improvement of the existing institutional and legal solutions and corrections of their model which remains the same all the time despite the fact that a succession of its versions have proved inefficient in practice.Taking the subject up, I adopted an entirely different approach and method of research. I assumed that all assistance can only be successful if those involved in it are genuinely motivated to that activity. Even if the norm „help the prisoners” is an element of the system of moral directives recognized in our culture, this fact alone by no means determines in advance the actual range and validity of that norm. Like all moral values, also this one is valid with different force, to a different  extent and has a different range for different people. For some, it is a postulate that needs to be fulfilled which they experience as a moral  obligation; for others, it is a criterion of axiological orientation. This implies the different ways of their functioning. As shown by analysis of empirical studies, the norm demanding that prisoners should be helped is not too deeply rooted in social consciousness. It has failed to win general acceptance even at the verbal level, and the readiness to fulfill it through a person’s own activity can be found but occasionally; in such cases, it is motivated situationally rather than by axi axiological experiences. The reason is probably that a moral appraisal of the object of assistance (an imprisoned offender) is transmitted to the appraisal of the duty to fulfill a norm. Instead of deciding whether help is at all necessary, we want to know if the person in need of help deserves to be helped. In so doing, we forget that all those objectively in need of help are worth being helped; we condition our decision as to rendering help upon the actualreason of a person’s helplessness, or more strictly speaking, upon  the rank on the moral scale of the acts that made that person helpless.In this situation, what becomes a signicificent factor that has a beartng on the discussed norm is the perception of un offender as a dewiant of a definite type. An offender is usually perceived through a stereotype: a specific conglomerate of simplified and mainly unfounded beliefs. Yet that very stereotype functions as a standard basing on which the actual way of conduct is chosen.Therefore, I tried to define the stereotype of an impriosoned offender that functions in social consciousness and in consciousness of professionals involved in the work with prisoners. I also tried to diagnose the psychosocial mechanism that result in the formation and consolidation of that stereotype.Which social groups and individuals tend to consider the postulate of assistance to prisoners as a norm that they themselves should follow, or at least which such groups and individuals have the strongest motivation to respond to that call?Of the many hypotheses about the origin of prosocial behaviour (and of course of helping which is a form of that behaviour), let us first consider the one which states that prosocial behaviour results from the structure of ,,ego” and the parallel observation that another person at a disadvantage is similar to oneself in some respect. That similarity may concern both the bodily and spiritual structure and all the other components of one’s self-image. Thus diagnosed, the similarity releases or at least catalyzes the readiness to prosocial behaviour. Basing on this hypothesis, it should be assumed that ex-offenders, ex-convicts, or generally speaking, persons affected by imprisonment are particularly likely to recognize that norm, and further, that the motivation to help prisoners growth with a reduced distance between the offender and the cultural circles that approximate him with respect to mentality and custom.Considering this hypothesis, we come across still another dependence: the actual condemnation of an offender depends on the degree of acceptance of the normative system which that offender has infringed. The discrepancy between values protected by law and the individual or group preferences results in a change in attitudes. A person convicted by force of a disapproved law is perceived as a victim and not an enemy. The offender thus meets with fellow-felling, and the authors and executors of the disapproved law, with resentment. This dependence, cannot be limited to the subcultural negation of law that is characteristic of criminal circles. It follows from the division of the bulk of crime into mala per se and mala prohibita. After all, stigmatization takes a different, course in the case of an obvious evil vs. one that is simply considered evil by law which cites reasons that are by no means necessarily either obvious or good, or which is directed against an interest that is not perceived in accordance with the official standpoint. Prohibitions lacking the proper axiological foundation proliferate with the instrumental treatment of penal law, reduced to the role of political tool; in such situations, all public activity of any importance whatever is usually subordinated to politics.What significantly differentiates the extent to which the norms that concern helping others are perceived as valid are the emotional and social bonds (e.g. fomily ties). From the psychological viewpoint, they constitute a particularly active and natural stimulator of motivations, one that defines the actual circle of the most involve addressees of the norn. In this case, the one who helps is not only personally interested in the fates of the one who gets help, but also acts for his own good  rendering that help. The social situation resulting from imprisonment of a family member gives rise to special problems in the legal, economic and social sphere. Quite obviously, the other members of that family should be allowed to participate in the solution of those problems which  are also their own.We have therefore distinguished the groups that are willing, as can be expected, to adopt the norm of helping prisoners and to act accordingly. Of course, we deal here with a selective range of that norm’s validity which is subject to a double limitation: not everybody is willing to help prisoners, and that readiness does not concern all prisoners. This follows from the contents of the discussed hypothesis which after all assumes the similarity of partners in interaction as the necessary condition of emergence of motivation.The fact that a person considers a definite behaviour his/her duty may as well result from that person’s internalization of certain moral norms or ideals that can only be fulfilled through such behaviour (the love of one’s fellow man, brotherhood, general kidness). What is released here, as opposed to the hypothesis discussed above, is a general sense of duty not related to any definite person or situation but directed at all those in need of help. The group of thus motivated person includes possible addressees of the norm helping prisoners. With ages, the social practice formed a variety of forms of orginization of those who treat assistance to prisoners as a moral norm. Concerned here are initiatives based initially on the model of charity and constituting part of the general charitable activities. In the l9th century, they developed into specialized patronage societies which in turn acquired, and preserved till the present day in the world, the status of an indispensable element of the rational prison system.The Polish model of society’s participation in the execution of the sentence of imprisonment eliminated all the above-mentioned subjects  from any activities whatever on behalf of prisoners. Finding this situation irrational, I tried to investigate its causes and to disclose the motives of those who had made it that way. Depending upon the object that serves as the system of reference for prosocial behaviour, that behaviour can be divided into allocentric and sociocentric. The allocentric behaviour is activity undertaken for reason of another person’s interests, i. e. aimed at securing the best possible functioning, protection, or development of that person. If, instead, the subject acts on behalf of an institutional or group, that is if the addressee of his/her action is a definite social arrangement, we deal with the sociocentric prosocial behaviour. This latter motivation was adopted in Poland as the basis for designing the institutional structures charged with the task of helping prisoners. Namely, after-care was inserted in that particular segment of criminal policy which is called in the legal language ,,participation of the community in crime prevention and control”. The term community used here expresses the principle of joint action. The whole means a specific kind of participation aimed at assisting the police, courts, and prison administration. As opposed to voluntary associations of those interested in helping prisoners and to patronage societies, such institutions are organized from without, follow the orders of State administration, base membership on the principle of  delegation or nomination, are organizationally included in the system of State agencies whose activities they supplement within their imposed competences, and are fully controlled by those agencies. Thus organized, the voluntary forces are used to support the machine involved in carrying out penalties; they become advocates of the so-called social interest and executors of the official State policy.The main conclusion that follows from the present study resolves itself into a postulate for a reform which would make it possible also, and perhaps in particular, for those with the allocentric motivation to become engaged in helping prisoners.